A Bibliometric Analysis of Ocean Plastic Pollution Research: Trends and Future Directions - Judijanto, Loso (Westscience Press, 2025)
This study presents a comprehensive bibliometric analysis of global research on ocean plastic pollution to identify key trends, influential contributors, thematic structures, and future research directions. Bibliometric data were retrieved from the Scopus database, covering the period from 2000 to 2024. Using VOSviewer, the study analyzed co-authorship networks, keyword co-occurrences, and temporal evolution of research themes. The analysis included publication trends, authorship patterns, country collaborations, and research clusters. The results reveal a substantial increase in research output, with dominant themes clustering around marine pollution pathways, microplastic impacts, environmental monitoring, and waste management strategies. Keywords such as “plastic pollution,” “microplastic,” and “environmental monitoring” were central to the field. Influential authors included Jambeck J.R., Law K.L., and Thompson R.C., while the United States, the Netherlands, and Canada emerged as leading countries in terms of productivity and collaboration. Recent research trends show a shift toward sustainability, climate linkages, and circular economy frameworks. The field is transitioning from problem identification to integrated solutions and policy-oriented approaches. Future research should strengthen interdisciplinary integration and promote more inclusive international collaborations, particularly involving regions most affected by marine plastic pollution. This study provides a systematic, visualized mapping of the ocean plastic pollution research landscape and offers strategic insights for academics, practitioners, and policymakers seeking to advance sustainable marine environmental governance.